Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.15605/jafes.038.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Awareness and its Relationship to Sociodemographic Characteristics of Filipino Adults: A Survey among Work-From-Home Employees in Metro Cebu, Philippines

Abstract: Objective. Awareness and substantial understanding of obesity are essential components in its prevention and treatment. This study aimed to determine the degree of obesity awareness and its relationship to various sociodemographic characteristics among Filipino adults working from home (WFH).Methodology. This is a cross-sectional survey conducted in Metro Cebu, Philippines. Included were non-healthcare WFH professionals aged 18-64. Researcher-made Obesity Awareness Questionnaire (OAC-20) was used.Results. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Our data support the known difficulties in self-perception of the disease in people suffering from obesity. In a recent publication that has evaluated obesity awareness and its relationship to sociodemographic characteristics ( 13 ), a significant relationship between higher educational attainment and obesity awareness has been shown, underlying that obesity awareness is significantly related to socioeconomic status and that the higher the household monthly income, the higher the level of awareness ( 14 ). In our study only half of the patients correctly identified themselves as being affected by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the known difficulties in self-perception of the disease in people suffering from obesity. In a recent publication that has evaluated obesity awareness and its relationship to sociodemographic characteristics ( 13 ), a significant relationship between higher educational attainment and obesity awareness has been shown, underlying that obesity awareness is significantly related to socioeconomic status and that the higher the household monthly income, the higher the level of awareness ( 14 ). In our study only half of the patients correctly identified themselves as being affected by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, being overweight has been shown to have a detrimental influence on physical health, mental health, and quality of life (Lin, 2019). Environmental and societal development has led to changes in health, agriculture, food and nutrition, marketing, and education, which have resulted in these dietary and physical activity modifications (Gao, 2018). Moreover, the levels of individual characteristics, the intricate nature of childhood obesity, recognizing individual characteristics and the influence of both direct and indirect, and the complex ways in which these experiences interact with each other to influence the child's development, even if the child is not directly involved in them, as contributing factors all contribute to the development of childhood obesity according to Bronfenbrenner's ecological theory and Reifsnider's epidemiology models (Taghizadeh, et al, 2023).…”
Section: The Obesity and Overweightmentioning
confidence: 99%
“…However, after Agudo and Gutierrez (2021), compared obese learners with normal students, obese and overweight learners do not appear to perform differently than normal-weight students, but they may be less pleased with life and their health state, have a lower body image, and are more likely to face social isolation and bullying. Obesity is common among Filipinos and is associated with a higher risk of hypertension, and diabetes (Toledano, et al, 2022). Gatillo, et al, 2022 stated that the obesity prevalence in the Philippines has gradually increased, with three out of every ten adult Filipinos being overweight or obese.…”
Section: The Obesity and Overweightmentioning
confidence: 99%